Industrial cutting of textile materials - Vilumsone-Nemes, Ineta; Textile Institute (Manchester, England) (Cambridge : Woodhead Pub Ltd, 2012)
A cutting room is a separate area in a clothing manufacturer where garment components are cut out. The accuracy and efficiency of cutting room operations is critical to all subsequent operations and to final garment quality. Drawing on the author's extensive experience, Industrial cutting of textile materials summarises good practice in cutting room operations. After an introduction, the author reviews initial steps such as unloading, sorting and quality control of materials. She then discusses subsequent operations from lay planning and marker making, through manual and automated spreading and cutting, to fusing of cut components and final work operations such as sorting cut components for sewing. Dr Vi?umsone-Nemes also discusses marker making, spreading and cutting of more intricate fabrics such as striped fabrics and fabrics with check, motif and border patterns, narrow lace and pile fabrics. Industrial cutting of textile materials provides essential knowledge about cutting processes to designers, technologists, and managers to help in improving product quality and in controlling production processes effectively. Summarises good practice in cutting room operationsReviews initial steps such as unloading, sorting and quality control of materials and discusses subsequent operations from lay planning and marker making to fusing of cut components and final work operationsIncludes coverage of more intricate fabrics such as striped fabrics and fabrics with check, motif and border patterns, narrow lace and pile fabrics.
6.10 Links to recommended websites7 The manual textile cutting process; 7.1 Introduction; 7.2 Characteristics of the manual cutting process; 7.3 Notches and cloth marking drills; 7.4 Accuracy problems in the manual cutting process; 8 Manual cutting equipment in textile cutting operations; 8.1 Introduction; 8.2 The straight knife cutting machine; 8.3 The round (rotary) knife cutting machine; 8.4 The small round knife cutting machine; 8.5 The band knife cutting machine; 8.6 The fabric drilling machine; 8.7 The hot notching machine; 8.8 Links to recommended websites.
Published in collaboration with the Textile Institute.
Keywords: Textile industry; TECHNOLOGY & ENGINEERING -- Technical & Manufacturing Industries & Trades; Textile industry